Effect of Integration of Arts on Achievement of Learners in Social Science - KAMATH, ASHA K.V.D (THE PRIMARY TEACHER, 2014)
Social science is one of the school subjects and is a content loaded subject which is hardly integrated by the teachers. Students find it not only heavy but also boring. Making a social science class interesting and participatory and reducing the energy consumed for understanding the content is a challenge for the teachers. While discussing about approach to pedagogy, NCF–2005 states that teaching of social science must adopt methods that promote creativity, aesthetics and critical perspectives. Art Education which covers four main streams namely, music, dance, visual arts and theatre is one such subject that when integrated with any other subject, makes the class lively, participatory and creative. NCF–2005 emphasises that learning of any of these arts would enrich the lives of our young citizens, not only in their school years but also throughout their lives. It further says that dramatisation is one of the under-explored strategies that could be employed. that Art Education improves academic study, communication and cognitive skills, impacting achievement in other areas. Therefore, the researcher felt the need to make social science class interesting, participatory, creative and to go beyond the textbook giving primacy to learners’ experiences. As normally students are interested in Arts, the researcher attempted to study the effect of two of the streams of Arts i.e., Drama and Visual Arts on achievement in social science. It was a two group pre-test post-test experimental study. The sample was two sections of Class VIII of a school following CBSE syllabus. While in one section learning process was mainly Dramatisation, in another section it was through Visual Arts. The findings of the study were: there is significant difference between the pre-test and post-test scores of both the groups which learnt the content by Dramatisation and Visual Arts. There is no significant difference in the achievement of the two groups who were exposed to Dramatisation and Visual Arts when comparing their gain scores. There is significant difference in terms of gain scores in the achievement of girls and boys who were exposed to Visual Arts. There is no significant difference in terms of gain scores in the achievement of girls and boys who were exposed to Dramatisation